Valproic acid and ivermectin increase GABA levels to improve the viability of skin flaps in rats - Pradnyandari, Gusti Ayu Putu Ratih; Riasa, I. Nyoman Putu (International Journal of Research in Medical Sciences, 2024)
Background: Gamma-aminobutyric acid (GABA) is a nonproteinogenic amino acid known as the main inhibitory neurotransmitter in the central nervous system. Ivermectin (IVM) and valproic acid (VA), both increase GABA levels. The purpose of this study was to determine the effect of VA and IVM on the viability of extended random-pattern skin flaps in Wistar rats and their GABA-dependent mechanisms. Methods: This experimental study used 32 Wistar rats that underwent surgery to have caudally based extended random-pattern skin flaps divided into four distinct groups. In the first group, 0.05 mg/kg IVM was administered via intraperitoneal (i.p.) injection 30 minutes (min) prior to elevating the flap. The second group was administered 100 mg/kg VA by i.p. injection 60 min prior to elevating the flap. The third group was administered VA 100 mg/kg followed by IVM 0.05 mg/kg injected (i.p.) 60 min and 30 min prior to flap elevation, respectively. The fourth group was used as a control. After 7 days, the percentage of flap viability was measured, and tissue sampling was performed to examine GABA levels. Results: It was found that the highest viability rate was in the group administered VA combined with IVM (93.98%) compared to all other groups (p<0.001). The highest GABA levels in the tissue were observed in the group administered VA combined with IVM (284.91 nmol/l) compared to all other groups (p<0.001). Conclusions: IVM in combination with VA improves the viability of extended random-pattern skin flaps by increasing GABA levels.